(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The Generalized Finite Element Method (GFEM) has been developed with the purpose of overcoming some limitations inherent to the Finite Element Method (FEM), related to problems that require remeshing. FEM solution space is enriched with a priori known information through the Partition of Unity (PU) at GFEM. Certain obstacles related to the nonlinear analysis can be mitigated with the use of GFEM and the damage and plasticity fronts can be represented. A FEM computational environment has been previously expanded with the enclosing of the GFEM formulation to linear analysis with minimum impact in the code structure and with requirements for extensibility and robustness. Such environment, so-called INSANE (INteractive Structural ANalysis Environment), is an object-oriented system that allows linear and nonlinear, static and dynamic structural analysis. Numerical simulations applying an elastoplastic damage constitutive model are carried out aiming to demonstrate the versatility of the code related to the application of such a constitutive model and GFEM.